Air pollution in Malaysian furniture industry / Izyan Lyana Mohd Mokhtar - Mohd Mokhtar, Izyan Lyana (2012)
Air pollution addition of harmful substances to the atmosphere resulting in damage to the environment. human health. and quality of life. Air pollution makes people sick. it causes breathing problems and promotes cancer and it harms plants animals and the ecosystems. Through a study conducted by the Department of Environment (DOE). air pollution is caused by emission, industrial activities and open burning. However, the few studies on the furniture factory shows that the performance of air pollution is lower than other activities that are level 0-50 according to the air pollution index (API) issued by the Department of Environment (DOE). This means low pollution and does not cause adverse health effects of factory workers and nearby residents.